Higher Educational Institution (HEI) Promotional Management Support System Through Sentiment Analysis for Student Intake Improvement - Sabar Aritonang Rajagukguk; Harjanto Prabowo; Agustinus Bandur; Rini Setiowati (IEEE Access, 2023)
Promotional activities with Emotional Intelligence (EI) are more effective than factual information. It is significant in Higher Educational Institutions (HEIs) marketing and reputation management. Choosing an HEI is a crucial decision. Factual information ignites the human brain’s analytical characteristics, making logical decisions while choosing an HEI. Promotional activities that target the emotional states push the target group to overlook logic and make emotional decisions. This paper presents a novel HEI Promotional Management Support (PMS) system that utilizes this phenomenon through sentiment analysis to enhance marketing capabilities. A Bi-Directional-Long-Short-Term-Memory (BiLSTM) network has been designed and implemented in this paper to classify the existing students’ sentiments into four classes. It classifies the sentiment with an average accuracy of 92.75%. The positive sentiment of the students is used to target the promotional content, whereas negative sentiment guides to avoid content that has the probability of raising negative concerns. The application of this novel PMS system demonstrates a 4.78% improvement in student intake over an observational period of 24 months. The unique concept, effective implementation, and remarkable result indicate that the proposed HEI Promotional Management Support System is a revolutionary application of Artificial Intelligence (AI) to improve student intake rate.